PENGARUH IMPLEMENTASI ASSET LIABILITY MANAGEMENT TERHADAP RISIKO MODAL PADA PERUSAHAAN-PERUSAHAAN SUB SEKTOR PERBANKAN DI BURSA EFEK INDONESIA (BEI) - B31112108, Novita Rahayu (Jurnal Manajemen Update, 2016)
Commercial Bank is a bank which is conducting conventional business orbased on syariah principles, in its activities the bank providing services in a traffic payment. In Indonesian law number 10 year of 1998 about banking, the bank which called as entities raise funds from the public in the form of savings and channel them to the public in the form of credit or other forms in order to improve people's lives. The purpose of this study to determine the effect of implementation of Asset Liability Management to the Risk Capital in Enterprises in Sub Sector of Banks listed in the Indonesia Stock Exchange (IDX). The research sample numbering 20 in the bank listed on the Indonesia Stock Exchange (IDX). The sampling technique used was purposive random sampling. The analysis tool used was multiple linear regression. The results of the study showed that the Interest Sensitive Rate and Return on Asset was positive influential and significant effect on the Capital Risk, the Non Performing Loans was influence positive effect on the Capital Risk. While Loan to Deposit Ratio was negative influence and significant on the Risk Capital. Keywords: Interest Sensitive Rate, Non Performing Loan, Return On Assets, Loan to Deposit Ratio, Capital Risk